Comparing Sleep Quality and General Health Among the Elderly Living at Home and at Nursing Home - Mansour Beyrami; Jaber Alizadeh Goradel; Servin Ansarhosein; Nasim Ghahraman Moharrampour (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: Survey about the issues and problems related to elderly in order to improve their quality of life of this increasing population has become a universal concern.This study was performed by the purpose of comparing the sleep quality and general health among the Elderly Residing at Home and Old People's Homes. Methods & Materials: This study is descriptive-analytic type. Population of this investigation consisted of elderly men and women (upper than 60 years old) living at personal home and at nursing home in Tabriz. Sample group composed of 100 elderly (50 men and 50 women 50 living at home and 50 living at nursing home) who were selected through available sampling method. For collecting data, Goldberg General Health Questionnaire and Pittsburgh Sleep Quality Index were used. Data were analyzed by Multivariate analysis of variance (MANOVA). Results: Findings showed that In terms of general health and its components (Physical symptoms, anxiety, social dysfunction and depression) and Sleep quality and its components (Subjective quality of sleep, time for sleep, total sleep time, sleep efficiency, routine, sleep disorders, sleep medications and daily dysfunction) there were significant differences between nursing home residents and elderly residents in nursing homes (P=0.001). Conclusion: Findings indicated that elderly residents in nursing home are experiencing more symptoms of anxiety, depression, physical symptoms and social dysfunction Compared with the elderly whom resident at home. Also the results showed that the elderly residents of nursing homes have poor sleep quality than ones whom residents at home. On the other hand Future development of elderly care institution is inevitable. Therefore, more attention to the living conditions of elderly residents of institutions seems necessary.